Children with Special Health Care Needs, Supplemental Security Income, and Food Insecurity. Issue 2 (February 2016) - Rose-Jacobs, Ruth; Goodhart Fiore, Jennifer; Ettinger de Cuba, Stephanie; Black, Maureen; Cutts, Diana B.; Coleman, Sharon M.; Heeren, Timothy; Chilton, Mariana; Casey, Patrick; Cook, John; Frank, Deborah A.
ABSTRACT: Objectives: To assess food insecurity in low-income households with young children with/without special health care needs (SHCN) and evaluate relationships between child Supplemental Security Income (SSI) receipt and food insecurity. Methods: A cross-sectional survey (2013–2015) of caregivers was conducted at 5 medical centers. Eligibility included index child age <48 months without private health insurance and a caregiver fluent in English or Spanish. Interviews included sociodemographics, 5-item Children with Special Health Care Needs Screener, 18-item US Food Security Survey Module, household public assistance program participation, and child SSI receipt. Household and child food insecurity, each, were evaluated using multivariable logistic regression models. Results: Of 6724 index children, 81.5% screened negative for SHCN, 14.8% positive for SHCN (no SSI), and 3.7% had SHCN and received SSI. After covariate control, households, with versus without a child with SHCN, were more likely to experience household (Adjusted odds ratios [AOR] 1.24, 95% confidence intervals [CI], 1.03–1.48) and child (AOR 1.35, 95% CI, 1.11–1.63) food insecurity. Among households with children with SHCN, those with children receiving, versus not receiving SSI, were more likely to report household (AOR 1.42, 95% CI, 0.97–2.09) but not child food insecurity. Conclusion: Low-income households with young children having SHCN are at risk for food insecurity, regardless of child SSI receipt and household participation in other public assistance programs. Policy recommendations include reevaluation of assistance programs' income and medical deduction criteria for households with children with SHCN to decrease the food insecurity risk faced by these children and their families.